2021
DOI: 10.1016/j.jcf.2021.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cystic fibrosis arthropathy: Data from the German cystic fibrosis registry

Abstract: Background: Epidemiology and potential risk factors for cystic fibrosis arthropathy (CFA) were studied in a relevant cystic fibrosis (CF) patient cohort.Methods: Cohort study of patients included in the German CF registry in 2016-2017. Descriptive analysis, exploratory tests and multivariable logistic regression were used to assess prevalence of CFA and associated potential risk factors for adult patients with/without chronic Pseudomonas aeruginosa infection.Results: 6069 CF patients aged from 0 to 78 years we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…We also reported that patients suffering from spinal and/or joint pain had significantly more frequent F508 homozygous mutations (59 vs. 24%, p = 0.014). By contrast, two previous studies didn't find an association between cystic fibrosis transmembrane conductance regulator (CFTR) mutations and CFA (7,9).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…We also reported that patients suffering from spinal and/or joint pain had significantly more frequent F508 homozygous mutations (59 vs. 24%, p = 0.014). By contrast, two previous studies didn't find an association between cystic fibrosis transmembrane conductance regulator (CFTR) mutations and CFA (7,9).…”
Section: Discussionmentioning
confidence: 76%
“…The comparison with other studies is difficult in the absence of an accepted definition of CFA and with various study designs. These studies described a prevalence of inflammatory joint included between 2 and 29% of the patients ( 6 – 9 , 28 ). In Koch et al study there was no significant difference regarding inflammatory signs such as joint swelling or warming between CF patients and controls ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For patients with cystic fibrosis (CF), less information is available in field literature, and some studies point to an overall lower incidence of SARS-CoV-2 infection in this patient population [ 1 , 2 ], but a higher rate of hospitalization among them [ 3 ]. Furthermore, once infection does occur, the patient is considered to be at risk of severe COVID-19 and this risk may be dependent on the underlying degree of lung damage, and also the degree of pancreatic or liver damage [ 4 ].…”
Section: Introductionmentioning
confidence: 99%